PARTISIPASI PUBLIK DI KOTA BEKASI DALAM PEMILU 2019 - Ali Syaifa AS (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2022)
The 2019 election was the first simultaneous election held in Indonesia since the first election was held in 1955. Simultaneously here in the sense of legislative elections together with the implementation of presidential and vice presidential elections. So that in the 2019 election voters get five types of ballots. This simultaneity creates its own challenges in the holding of the 2019 elections. Both in terms of the technical implementation of voting and vote counting. Also in terms of community enthusiasm or community participation. In practice, although the voting and counting have experienced complexity because of the large number of votes that must be used by voters and take a lot of time when counting votes at polling stations (TPS). However, the good news is that the results of the voting and counting are the achievement of greater public participation from the previous elections. In the data records in the Bekasi City KPU, Community Participation for the Election of President and Vice President is 76.1% and for the Legislative Election is 75.8%. Even if it refers to the target of participation suspected by the Indonesian KPU it has not been achieved. The participation target announced by the Indonesian KPU is 77.5%. However, through a number of socialization efforts carried out by the Bekasi City KPU, public participation in the 2019 elections can increase.